Effect of human umbilical cord mesenchymal stem cells on ovarian function in lupus mice. Issue 4 (30th October 2022) - Meng, Defang; Xie, Jing; Li, Hui; Tang, Yu; Wei, Hua
Abstract: Background: Patients with systemic lupus erythematosus (SLE) suffer from a high incidence of premature ovarian failure, which might be due to cyclophosphamide gonadal toxicity, immune abnormalities, or other reasons. This study aimed to investigate whether the transplantation of human umbilical cord mesenchymal stem cells (HUC‐MSCs) can improve ovarian reserve function in lupus mice. Methods: We used MRL/lpr mice to observe changes in ovarian structure and secretory function in SLE. Lupus mice and controls were injected with HUC‐MSCs at Weeks 12 and 16. We detected serum concentrations of the sex hormones estradiol (E2), follicle‐stimulating hormone (FSH), and anti‐Müllerian hormone (AMH), using enzyme‐linked immunosorbent assays. Hematoxylin and eosin staining showed ovarian tissue structure and enabled the counting of follicles. Hepatocyte growth factor (HGF) and insulin‐like growth factor 1 (IGF‐1) expression in ovarian tissue was observed by immunohistochemistry. Results: Ovarian function in lupus mice was abnormal, as indicated by decreased serum E2 and AMH concentrations, and increased FSH concentrations. HUC‐MSC transplantation caused significant upregulation of serum E2 and AMH and downregulation of FSH (all p < 0.05). Ovarian structure improved and the follicle number increased after HUC‐MSC transplantation. Multiple infusions of HUC‐MSCs at Weeks 12 and 16 resulted in a significantly higher number of primordial follicles than infusions of HUC‐MSCs at only Week 12 ( p < 0.05). Immunohistochemistry showed that IGF‐1 and HGF expression increased after HUC‐MSC transplantation, but this was not significant. Conclusions: HUC‐MSCs transplantation restores disturbed hormone secretion and folliculogenesis in lupus mice. HUC‐MSC transplantation should be repeated for the best treatment effect. Abstract : Human umbilical cord mesenchymal stem cells (HUC‐MSCs) transplantation restores disturbed hormone secretion and folliculogenesis in lupus mice. Key points: Ovarian function in lupus mice was abnormal with disturbed hormone secretion and folliculogenesis and human umbilical cord mesenchymal stem cell transplantation could recover ovarian function in lupus mice. Systemic lupus erythematosus (SLE) itself may have an abnormal ovarian function. We also suggested novel strategies to treat patients with SLE with premature ovarian failure.